An evaluation of pediatric forensic trauma cases: a retrospective study (Annals of Medical Research, 2021)
Aim: Forensic trauma has become frequently seen in Emergency Departments and these injuries can leave significant sequelae reaching a life-threatening degree and may even result in death. Through retrospective examination, the aim of this study was to define the frequency of forensic trauma cases presenting at our clinic in one year, to reveal the outlook of our region with references to relevant epidemiological data, and to provide guidance on the approach to be taken by physicians encountering these cases.